The influence of auditor characteristics on audit quality - Pais, C.; Machado, F. (2021 16th Iberian Conference on Information Systems and Technologies (CISTI), 2021)
Most of the literature on audit quality is at a firm and office level. Here, we analyse the influence of several auditor characteristics on audit quality, namely gender, education, education area and experience, in a European setting. Based on a sample of STOXX® 600, we find evidence that auditors’ gender and education influence audit quality, the former decreasing discretionary accruals if the auditor is female and the latter increasing audit fees for higher degrees. These results may be due to the fact that female auditors are more interested in the audit quality (being more risk averse, more intense in the cognitive process and less overconfident than male auditors) than in the aspects of the audit firm’s business. Moreover, the higher the level of education, the more knowledge auditors have to perform an audit and this is noted by the market. This study contributes to the existing literature on audit quality by studying auditor attributes and stressing the importance of gender and education in audit quality.